Educação não-formal e políticas públicas para o fortalecimento da democracia: o processo de capacitação das agentes comunitárias de saúde e das agentes de proteção social, da Prefeitura de São Paulo, em educação ambiental associada à saúde - Manhas, Cleomar Souza (2008)
The research Non-Formal Education and Public Policies: Democracy Invigoration: The capacity process of the Health Community Agents and Social Protect Agents, by São Paulo Local Government, in environment education associated to health had as objective the verification of the non-formal education process utilization on the implementation of the public social policies looking if these kind of process contribute to the democracy maturing. The understood democracy in this research as participative democracy in the critical acceptation of the participative processes, or the community participation contributing to the social emancipation and the consequent society position by the State.The research methods were semiparticipative because we shared the first phase or the implementation phase besides we realized interviews and documental analyses.Our theory horizon was based on the emancipation of the third pillar modernity sustentation proposal or the Community according to Boaventura de Sousa Santos; the possible construction of the Liberty Ethic according to Enrique Dussel and the community conscience proposed by Paulo Freire